(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Students’ weak mathematical metacognitive skills can reduce their drive to learn, potentially leading to underwhelming outcomes in mathematics. This study investigated mathematical metacognition levels among high school students and examined potential gender differences. A quantitative approach was employed, surveying 402 randomly selected students from four secondary schools of Kathmandu district. Metacognition was assessed using 18 items adapted from the Junior Metacognitive Awareness Inventory (Jr MAI). Results revealed strong student awareness of interest impacts on learning but weak engagement in self-questioning about outcomes. Significant gender differences emerged, with males demonstrating higher overall metacognition scores (mean = 67.655) compared to females (mean = 64.399), (t = -2.875, p = 0.004, d = 0.2886). Girl students exhibited greater inconsistency in metacognitive abilities. The study highlights the need for targeted interventions considering both general metacognitive development and gender-specific approaches. Implications include adapting teaching strategies to individual metacognitive awareness levels and developing interventions for areas of lower usage. Future research should explore factors contributing to gender differences and investigate effective strategies for promoting metacognitive development across all students, regardless of gender.